Who Are You, Mrs Walter Shandy, Aberratio Naturae? - Łowczanin, Agnieszka (Text Matters: A Journal of Literature, Theory and Culture, 2011)
The aim of this paper is to examine the critically unacknowledged aspect of the canonical Tristram Shandy by Laurence Sterne: the authorial delineation and narrative management of the character of Mrs Shandy, who is a silent presence in the background even though the pivotal personal events for the narrator of this spoof-autobiography are his conception and birth. The novel, otherwise thoroughly structurally and thematically experimental, seems to be fossilized in the ancient and Christian philosophers’ assumptions about the physical incompleteness of the "weaker vessel" and the malign influence of her disturbing physiology, which for centuries fed into the ontological concept of a woman as Nature’s aberration, aberratio naturae. Mrs Shandy’s muteness, a striking contrast to her husband’s verbosity, her absence and exclusion from the affairs of the male dominated household seem to run counter to the novel’s progressive form and linguistic audacity, the sociological shifts slowly taking root and medical discoveries made before and during this age of paradoxes.